Quality Assurance Study of Caries Risk Assessment Performance by Clinical Faculty Members in a School of Dentistry. Issue 9 (1st September 2014) - Rechmann, Peter; Featherstone, John D.B.
Abstract : The goal of this quality assurance study was to explore the decision making of clinical faculty members at the University of California, San Francisco School of Dentistry predoctoral dental clinic in terms of caries risk level assignment using the caries risk assessment (CRA) as part of the Caries Management by Risk Assessment (CAMBRA) concept. This research was done in part to determine if additional training and calibration were needed for these faculty members. The study tested the reliability and reproducibility of the caries risk levels assigned by different clinical teachers who completed CRA forms for simulated patients. In the first step, five clinical teachers assigned caries risk levels for thirteen simulated patients. Six months later, the same five plus an additional nine faculty members assigned caries risk levels to the same thirteen simulated and nine additional cases. While the intra‐examiner reliability with weighted kappa strength of agreement was very high, the inter‐examiner agreements with a gold standard were on average only moderate. In total, 20 percent of the presented high caries risk cases were underestimated at caries levels too low, even when obvious caries disease indicators were present. This study suggests that more consistent training and calibration of clinical faculty members as well as students are needed.